The Adjustment of Prices to Monetary Shocks when Trade is Uncertain and Sequential - Eden, Benjamin (Journal of Political Economy, 1994)
Trade is both uncertain and sequential. Money surprises are not neutral because prices at the beginning of the trading process cannot depend on its end. In contrast with fixed-price models, in this paper sellers can change prices during trade. In contrast with Lucas's article, here there is no asymmetry in the information about the money supply. The price quoted by individual sellers may adjust slowly to changes in the targeted money supply, but the distribution of quoted prices adjusts perfectly to these changes and the real price distribution is independent of the anticipated rate of change in the money supply.